Pemanfaatan Kearifan Lokal Orang Rimba di Jambi Melalui Pengembangan Bahan Ajar Untuk Meningkatkan Literasi Lingkungan Siswa - Siti Sriyati*; Pisca Hana Marsenda; Topik Hidayat (Jurnal Pendidikan Sains Indonesia, 2022)
Orang Rimba are one of the tribes in Jambi who live in the Bukit Duabelas National park (TNBD). Orang Rimba take advantage of the wealth of plants and animals that surround them. Orang Rimba have such strong customs that affect their lives and livelihoods. They have local wisdom in managing their environment. This study aims to utilize the local wisdom of the Orang Rimba through the development of teaching materials on Biodiversity to improve students' environmental literacy. The research method used is the development method with the ADDIE model (analyze, design, develop, implement, evaluate). The study began with a needs analysis to one of the senior high schools in Soralangun, which is a school adjacent to TNBD and field data collection to Orang Rimba in TNBD. At the implementation stage, a trial of teaching materials was carried out to students in one of the X grade high schools in Soralangun with a non-equivalent control group design. The instruments used in this study were interview guidelines, feasibility validation sheets, readability of teaching materials and environmental literacy instruments. The results showed that the teaching materials had an average feasibility of 81.66% (very feasible) and readability of 70.92% (high). The increase in environmental literacy of students in the experimental class showed an N-gain of 3.8 in the medium category